Atretic right superior vena cava with left superior vena cava draining directly into left atrium with absent coronary sinus in an adult with partial atrioventricular canal defect and complete heart block. Issue 9 (11th July 2020) - Mishra, Anand Kumar; Jaswal, Vivek; Kynta, Reuben Lamiaki; Bansal, Vidur; Kumar, Vikas; Singh, Rana Sandip
Abstract: The association of atretic right superior vena cava with persistent left superior vena cava draining directly into left atrium with absent coronary sinus in atrioventricular canal defect is virtually unknown in adults with no case reported so far. Though atretic right superior vena cava with persistent left superior vena cava is an extremely rare venous anomaly seen in congenital heart disease, it has important clinical implications in cardiac surgery and interventional cardiology. Atrial arrhythmias and right bundle branch block are common with advancing age in partial atrioventricualr canal defect but complete heart block has scarcely been reported in the medical literature.